Pemberian Latihan ROM dengan Bola Karet terhadap Kekuatan Otot Tangan Pasien Stroke Non Hemoragik - Ni Made Wedri; I Wayan Sukawana; I Made Sukarja (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2017)
The purpose of this research is to know the effect of ROM exercise with rubber ball on hand muscle strength of non hemorrhagic stroke patient. Research with pre-test design post-test with control group. Selection of nonprobability samples of purposive sampling type, 46 samples in RSUD Klungkung and RSUD Bangli. Average hand muscle strength before ROM training with rubber ball 4.5130 after 8.1696, average hand muscle strength before ROM practice without rubber ball 5.7261 after 6.9609. The result of Paired T test of treatment group was obtained p = 0,000 α (α = 0,05) and control group result p = 0,000 α (α = 0,05). The result of analysis of Independent T test value p = 0,000 0,05, concluded that there is influence of ROM exercise with rubber ball to hand muscle strength of non hemorrhagic stroke patient.